Holistic Policy Responses for Disability-Inclusive Disaster Risk Reduction: A Rapid Review - Mellifont, Damian; Villeneuve, Michelle; Nila, Farhana Haque; Crawford, Tonia; Subramaniam, Parvathi; Yen, Ivy (Departemen Ilmu Administrasi FISIP UNHAS, 2025)
People with disability can experience barriers to their safety throughout stages of emergency management planning, response, and recovery. To advance national policy guidance and social justice, this review asked how the application of national DiDRR principles and standards have shaped DiDRR policy and practice guidance external to Australia. Our rapid review thus informed the following two questions: a) what national DiDRR guiding principles, standards and related structural barriers currently exist outside of Australia?; and b) in what ways might national guiding principles and standards be practically applied in whole-of-government and whole-of-society policy efforts to address structural barriers impeding DiDRR? Applying thematic analysis, we identified nine national DiDRR principles: strength-based emergency support; human rights; equal partnerships; diversity and inclusion; cultural competence; anti-discrimination; accessibility; person-centred emergency preparedness; and education and awareness. Three national DiDRR standards covered accessibility across: emergency communication; emergency transport; and emergency shelter. Our exploratory research raises potential for co-designed DiDRR policy and practice to increase the social and economic participation of people with disability that extend beyond immediate goals of reducing emergency risks.